The Role of KDM2B and EZH2 in Regulating the Stemness in Colorectal Cancer Through the PI3K/AKT Pathway - Sanches, Jaceline Gisliane Pires; Song, Bo; Zhang, Qingqing; Cui, Xinye; Yabasin, Iddrisu Baba; Ntim, Michael; Li, Xinlong; He, Jiabei; Zhang, Yao; Mao, Jun; Lu, Ying; Li, Lianhong (Frontiers in Oncology, 2021)
Background: The incidence of colorectal cancer (CRC) has been increasing worldwide in recent years. Targeting cancer stem cells (CSCs) in CRC remains a difficult challenge. KDM2B and EZH2 play important role in the maintenance of CSCs' self-renewal capacity and tumorigenic ability; however, the biological functions of those genes in CRC remain unclear. In this study, we aimed to define the contribution of the expression of KDM2B in the features of CRC and establish the relationship between KDM2B and EZH2 in colorectal CSCs. Methods: The expression of KDM2B and EZH2 in the specimens of CRC and CRC cell lines were analyzed by immunohistochemistry, Western blot, and immunofluorescence. The underlying mechanisms of altered expressions of KDM2B and EZH2 and their impact on the biologic features of CRC and stemness in CRC were investigated. Results: The KDM2B gene was highly expressed in CRC tissues, and its overexpression positively correlated with tumor stages and tumor/node/metastasis (TNM) classification. The downregulation of KDM2B retarded cell proliferation, induced DNA damage, reduced spheroid formation, and decreased CRC stem cell markers: CD44, CD133, and ALDH-1. Moreover, the downregulation of KDM2B decreased the expression of EZH2 and both regulated cell migration, invasion, and stemness in the CRC cell line. Additionally, the interaction between KDM2B and EZH2 significantly increased the components of the PI3K/AKT pathway including AKT and PI3K. The high expression of KDM2B positively correlated with EZH2 in CRC tissues. Conclusion: This study shows that the downregulation of KDM2B and EZH2 can regulate CRC cell stemness, and their interaction may serve as a novel prognostic marker and therapeutic target for patients with CRC.